2007
DOI: 10.4319/lo.2007.52.5.2002
|View full text |Cite
|
Sign up to set email alerts
|

Frequent regime shifts in trophic states in shallow lakes on the Boreal Plain: Alternative "unstable" states?

Abstract: Shallow lakes are known to exhibit alternative states in their biotic structure. Lakes dominated by submersed aquatic vegetation (SAV) are ''clear,'' while lakes dominated by algae (high concentrations of chlorophyll a [Chl a]) are ''turbid.'' The roles of total phosphorus (TP) and SAV in defining these alternative states were examined for up to 6 yr in 24 naturally eutrophic shallow lakes (12.4-670.4 mg TP L 21 ) with variable SAV cover (0-100%) on the western Boreal Plain in Alberta, Canada. Clear lakes had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 42 publications
3
95
0
Order By: Relevance
“…) suggested to entail high risk of macrophyte loss in Yangtze shallow lakes (Wang et al, 2014) and the level (0.018 mg L −1 ) suggested as a threshold for a dominance shift from macrophytes to phytoplankton in Canadian lakes (Bayley et al, 2007). The relatively minor effect of nitrogen may be due to a weak development of periphyton compared with other studies showing a strong positive effect of nitrogen on periphyton growth (Özkan et al, 2010) and an associated decline in macrophyte growth (Olsen et al, 2015;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 50%
“…) suggested to entail high risk of macrophyte loss in Yangtze shallow lakes (Wang et al, 2014) and the level (0.018 mg L −1 ) suggested as a threshold for a dominance shift from macrophytes to phytoplankton in Canadian lakes (Bayley et al, 2007). The relatively minor effect of nitrogen may be due to a weak development of periphyton compared with other studies showing a strong positive effect of nitrogen on periphyton growth (Özkan et al, 2010) and an associated decline in macrophyte growth (Olsen et al, 2015;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 50%
“…At a local scale, the processes determining lake biological regimes include both top-down and bottomup interactions, and thus, it is crucial to examine the relative roles of different factors at different levels (Bayley et al 2007;Brönmark et al 2010;Hargeby et al 2007;Scheffer and Jeppesen 2007;Xu et al 2012). In terrestrial grassland ecosystems, local food web interactions have been shown to override temperature effects (Suttle et al 2007), and similarly, it has been experimentally demonstrated that changes in the local food web composition may alter the response to climate change (Hansson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In lakes where submerged plants cover almost the entire bottom surface, however, as is the case for Lake Kleszczów, it may be several times higher (Bayley et al, 2007). The threshold value is influenced not only by the vegetation cover, its composition, and seasonal dynamics of biomass, but also by the structure of ichthyofauna and contribution of planktivorous and piscivorous fish to the strength of top-down interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The year-round persistence of the submerged vegetation must have been of high importance for the lake with retention of nutrients in the plant biomass, even in winter, restricting the development of phytoplankton (Scheffer, 1998). Moreover, the continuous presence of macrophytes reduces the risk of e.g., cold conditions delaying the growth of submerged macrophytes in early spring, which could favour algal development (Blindow et al, 1993;Bayley et al, 2007;Sayer et al, 2010b;Hilt et al, 2013). Year-round vegetation provides rich resources of epiphytic fauna as food for fish, reducing their pressure on zooplankton (Diehl & Kornijów, 1998;Kornijów et al, 2005Kornijów et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation